The Value of Pre-Islamic Poetry in the Book of Bahjat Al-Majalis and Uns al-Majalis by Ibn Abd Al-Barr Al-Qurtubi (368-463 AH) - Ghidan, Jamal Ali (Journal of Arabic Language Sciences and Literature, 2025)
This study examines the value of pre-Islamic poetry contained in the Book entilted "Bahjat al-Majalis wa Uns al-Majalis" (The Joy and Convenience of Gatherings) by Ibn Abd al-Barr al-Qurtubi (368-463 AH). This is a three-pronged study. It addresses the stature of Ibn Abd al-Barr al-Qurtubi whose fame spread far and wide, where his works and opinions are emulated. It also examines the value and importance of the Book. Then, it tackles Ibn Abd al-Barr's mastery of pre-Islamic poetry, which he embodies in most of the Book's chapters. The researcher followed a descriptive and analytical approach in his study. Among the most important questions raised by this study are: What is the value of the Book's author and the Book itself? Moreover, what is the extent of Ibn Abd al-Barr's interest in pre-Islamic poetry in his Book? The study concludes that Ibn Abd al-Barr pays clear attention to pre-Islamic poetry in most of the chapters of his Book, citing: Documentation, explanation, tracing and authentication of meanings, approval and influence.The researcher recommends examining the critical standards followed by Ibn Abd al-Barr in his selections and representations of pre-Islamic poetry in its various meanings. He also recommends probing the human and artistic values in the poetry represented by the author of Al-Bahjah.
Keywords: the value of poetry; the pre-Islamic poetry; Bahjaht al-Majalis